Nuclear medicine methods in the assessment of acupuncture effects: a short review - Souza,Deise Elisabete (2007)
The mechanisms of acupuncture are poorly understood. In consequence, numerous investigators have conducted clinical trials to test the efficacy of acupuncture in various conditions. We have used PubMed database system to evaluate the number of publications in acupuncture and nuclear medicine procedures in the period from 1964 to 2007, using the keywords: "nuclear medicine and acupuncture", "SPECT and acupuncture", "PET and acupuncture", "scintigraphy and acupuncture", "radionuclide and acupuncture", "radiopharmaceutical and acupuncture", "radioisotope and acupuncture" and "99mTc and acupuncture". Some papers published in English language were selected and a short review is presented The analysis of the number of publications shows that when a method is well accepted by the scientific community, as the methods used in nuclear medicine, the interest in the development of research increases. Moreover, important findings are presented when the nuclear medicine image is used to evaluate the effect of the acupuncture.